"Peanut saves the day": an innovative solution to massive, cryptogenic haemoptysis—a case study. Issue 6 (7th May 2021) - Chetana Shanmukhappa, Sanjana; Lokeshwaran, Srivatsa; Kumar K, Sunil; Doraiswamy, Prakash
Abstract: Massive (or life‐threatening) haemoptysis is a time‐sensitive emergency encountered by a physician that requires an interdisciplinary, collaborative effort to arrest the bleeding in a prompt and timely manner. Placement of an endobronchial Watanabe spigot (EWS) to halt haemoptysis is a relatively recent technique finding its wide application in airway pathology, with the current extension of its use to bronchial bleeding. However, the lack of immediate access to EWS gives rise to the need to innovate with day‐to‐day materials used in routine surgical practice and available in resource‐limited settings, which may serve the purpose of a spigot. In this report, we bring to light a case of life‐threatening, cryptogenic haemoptysis that was managed by a novel technique of using peanut gauze as a spigot resulting in a successful endobronchial tamponade. Abstract : Massive (or life‐threatening) haemoptysis is a time‐sensitive emergency encountered by a physician. The lack of immediate access to an endobronchial Watanabe spigot gives rise to the need to innovate with day‐to‐day materials used in routine surgical practice and available in resource‐limited settings, which may serve the purpose of a spigot. In this report, we bring to light a case of life‐threatening cryptogenic haemoptysis that is managed by a novel technique of using peanut gauze as a spigot resulting in a successful endobronchial tamponade.